ANALISIS BIOEKONOMI DAN STRATEGI PENGELOLAAN HUTAN LESTARI DI SUMATERA DAN SUMATERA BARAT - Kardiman Kardiman (Fakultas Pertanian Universitas Borobudur, 2022)
The bioeconomy aims at decreasing reliance on fossil fuels, preventing or reducing climate change, eliminating insecurity, and efficiently using resources; however, fierce controversy exists on conceivable pathways to accomplish these objectives. The aim of this paper is to promote a dialogue as to whether an economy based on biomass can be more sustainable than today’s existing economies, considering that the economy needs to expand and be boosted, while creating a cascading and recycling system. This semisystematic review paper discusses two research questions based on findings from the last 20 years : 1. To Determine the actual and optimal utilization of Sumatera Land and West Sumatera in particular. 2. To find out the actual and optional the forest bioeconomic analysis in Sumatera and West Sumatera in particular. This article recommends following a strategy that is diverse regarding its approaches to shaping the bioeconomy and further funding of Sumatera’s forest and renewable energy sources, along with the involvement of urban planning.Keywords : sustainable bioeconomy; Deforestation and Degradation, renewable energy, Biomass.